Lecturers’ And Tesl Teacher Trainees’ Perceptions Towards The Level Of Readiness In Performing Teaching Practice - Jaafar , Haliza; Sreetharam, Shereena (2010)
Teaching practice is a course offered to teacher trainees of the Faculty of Education, Universiti Teknologi Malaysia. This course will enable the trainees to practice their teaching skills under the guidance of a supervisor. The research was carried out to investigate the effectiveness of the subjects taught to the teacher trainees before their teaching practice and to determine the level of readiness in terms of subject knowledge and subject competence of the teacher trainees. The respondents of this research were 34 and 39 third and fourth year TESL students respectively. The respondents were required to answer the questionnaires. Five lecturers who had taught the TESL programme and went out to supervise the teacher trainees from the Department of Modern Language (FPPSM) participated in the interview sessions. All the data obtained from the questionnaires and interview sessions were analyzed manually. The findings of this research proved that the exposure to the several subjects before teaching practice really helped the teacher trainees in performing their teaching practice. The teacher trainees were able to apply all the skills and techniques gained in the real classroom context. However, this research proved that many of the teacher trainees were not prepared in terms of subject knowledge and subject competence. Most of the trainees do not have deep understanding on subject knowledge and are still encountering problems in terms of their language proficiency. To conclude, the findings of this research offered some recommendations to further improve the performance of TESL teacher trainees during the teaching practice. The suggestions given would help the teacher trainees to enhance the level of readiness in terms of their subject knowledge and subject competence. This would enable the trainees to perform their teaching practice more effectively.